Students’ Learning Experiences and Preference in Performing Science Experiments Using Hands-on and Virtual Laboratory - Bugarso, John Marc S.; Cabantugan, Ramel E.; Tapiculin, Que-ann D.; Malaco, Amera C. (Universitas Pendidikan Indonesia (UPI), 2021)
This study investigated the hands-on and virtual laboratory learning experiences and laboratory preference of 91 students in performing science experiments. This study utilized a descriptive-correlation research design. The study revealed that students had positive learning experiences towards hands-on laboratory in terms of thinking, understanding, performing, and reasoning than in the virtual laboratory. Moreover, most of them highly preferred hands-on laboratories in terms of learning environment, motivation and enjoyment, stimulation of active learning, comfort, and convenience. The students’ preferences in the different laboratory settings were significantly different. Hence, there was a moderate correlation between students’ learning experiences and their laboratory preference in the hands-on laboratory. Meanwhile, there was a strong correlation between these two variables in a virtual laboratory. It is recommended to the educational institutions to enhance and strengthen their supports through providing complete laboratory facilities to the schools. Additionally, the teachers should continuously integrate laboratories to support the theoretical understanding of students in various science lessons. Importantly, the teachers and students should be innovative in performing experiments especially due to the limited instructional resources in this time of new normal.